Drying kinetics of passion fruit seeds - Santos, Hevellynn Hingreth; Rodovalho, Renato Souza; da Silva, Daniel Pereira; Morgado, Valdoméria Neves de Moraes (Científica, 2018)
After the extraction, passion fruit seeds present moisture content around 30% w.b., making their storage unviable. Thus, drying becomes an important tool for the safe storage of these seeds. Based on the study of the drying process, it is possible to obtain information regarding the phenomenon of heat and mass transfer between the product and the drying element, atmospheric air, heated or not. The objective of this work was to evaluate the drying kinetics of passion fruit seeds exposed to three drying conditions: full sun, half shade and shade (laboratory), as well as to determine their thermodynamic properties. The temperature was measured by means of a chemical thermometer (wet and dry bulb). For the validation of the drying equations, analysis of nonlinear regression of the mathematical models of drying to the experimental data was performed, the parameters of the models being related to the drying air temperature. The values of the coefficient of determination (R2), mean relative error (P), estimated mean error (SE), and chi-square (X2) were used as criteria to verify the fitting degree of the mathematical models studied. The Wang and Singh model was the model that best fit the experimental data, with R2 values closer to the magnitude, X2 and SE closer to 0 and smaller P. The sun drying condition obtained a greater efficiency in the water removal of passion fruit seeds.